El gasto público en el sector educación del departamento de Boyacá (2005-2012 - Acero Jiménez, Luis Enrique (Universidad Pedagógica y Tecnológica de Colombia, 2024)
Eng: This document aims to determine the efficiency of public spending on education in the department of Boyacá, for the period 2005-2012, for some key variables related to the sector. This document associated efficiency with increased of the educational system quality reflected in improved results achieved ICFES tests. In this sense, the document displayed as part of the Colombian State has been increased coverage rates in education at national level, departmental and local. However, such efforts have been questioned because the quality has been neglected. However, in the document is evidence that in the period of analysis, there have been efficiency in public spending directed towards the educational sector.